2018
DOI: 10.1111/eve.12892
|View full text |Cite
|
Sign up to set email alerts
|

Rostral mandibulectomy for treatment of a sarcoma in a 16‐year‐old Thoroughbred mare

Abstract: Summary A 16‐year‐old Thoroughbred mare presented with a 1‐year history of a growing mass on the rostral mandible. Biopsy performed by the referring veterinarian revealed chronic granulating fibrosis and stomatitis. Due to progressive loss of body condition and increasing size, the mare presented to the clinic. Radiographic examination of the mandible revealed osteolytic lesions. Mandibulectomy was performed under general anaesthesia. The horse's demeanour and feed intake improved significantly and the cosmeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Rostral mandibulectomy has been previously described (Richardson et al ; Mendez‐Angulo et al ; Kohler et al ) resulting in good cosmetic outcome. Rostral mandibulectomy in this case allowed for complete removal of the lesion from the mandible, without disturbing the mandibular symphysis and resulted in excellent cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…Rostral mandibulectomy has been previously described (Richardson et al ; Mendez‐Angulo et al ; Kohler et al ) resulting in good cosmetic outcome. Rostral mandibulectomy in this case allowed for complete removal of the lesion from the mandible, without disturbing the mandibular symphysis and resulted in excellent cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…The most common indication for rostral mandibulectomy are tumours of the rostral mandible (Dixon & Reardon, 2015; Easley et al, 2011; Nottle et al, 2021; Richardson et al, 1991; Witte, 2014), and ossifying fibroma is the most prevalent mass diagnosed in the rostral mandible (Nottle et al, 2021; Richardson et al, 1991). Ossifying fibroma is a locally invasive, proliferative, fibro‐osseous benign tumour that tends to grow rapidly and is typically reported in young horses (Nottle et al, 2021; Richardson et al, 1991) but has also been reported in elderly horses (Köhler et al, 2019; Nottle et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other tumours reported as an indication for rostral mandibulectomy are osteomas, fibrous dysplasia (Nottle et al, 2021), fibrosarcoma (Bass et al, 2017; Köhler et al, 2019), ameloblastoma (Mendez‐Angulo et al, 2014) and squamous cell carcinoma (Dixon & Reardon, 2015).…”
Section: Introductionmentioning
confidence: 99%